Targeting the SPC25/RIOK1/MYH9 Axis to Overcome Tumor Stemness and Platinum Resistance in Epithelial Ovarian Cancer - Xingyu Jiang; Muwen Yang; Weijing Zhang; Dongni Shi; Yue Li; Lixin He; Shumei Huang; Boyu Chen; Xuwei Chen; Lingzhi Kong; Yibing Pan; Pinwei Deng; et al. (Advanced Science)
Abstract In epithelial ovarian cancer (EOC), platinum resistance, potentially mediated by cancer stem cells (CSCs), often leads to relapse and treatment failure. Here, the role of spindle pole body component 25 (SPC25) as a key determinant promoting stemness and platinum resistance in EOC cells, with its expression being correlated with adverse clinical outcomes is delineated. Mechanistically, SPC25 acts as a scaffolding platform, orchestrating the assembly of an SPC25/RIOK1/MYH9 trimeric complex, triggering RIOK1‐mediated phosphorylation of MYH9 at Ser1943. This prompts MYH9 to disengage from the cytoskeleton, augmenting its nuclear accumulation, thus potentiating CTNNB1 transcription and subsequent activation of Wnt/β‐catenin signaling. CBP1, a competitive inhibitory peptide, can disrupt the formation of the aforementioned trimeric complex, diminishing the activity of the SPC25/RIOK1/MYH9 axis–mediated Wnt/β‐catenin signaling, and thus attenuate CSC phenotypes, thereby enhancing platinum efficacy in vitro, in vivo, and in patient‐derived organoids. Therefore, targeting the SPC25/RIOK1/MYH9 axis, which mediates the maintenance of stemness and platinum resistance in EOC cells, may enhance platinum sensitivity and increase survival in patients with EOC.